The Bologna process – a challenge to innovation in forest policy and economics education and research - Schmithüsen, F. (Український ордена "Знак Пошани" НДІ лісового господарства та агролісомеліорації ім. Г.М. Висоцького Держкомлісгоспу та НАН України, 2008)
The Bologna process will thrust forestry and forestry education into the context of an evolving global economy as well as worldwide concerns about environmental protection and climate change. It stimulates the integration of forestry into the framework of sustainable land-use practices and the combination of forest management experience with new scientific knowledge and research methodology. Forest professionals need a comprehensive educational background if they are to tackle rapidly changing social, economic and political problems. At the same time they need to understand the evolving and locally specific social and cultural aspects of forestry. This demands a joint approach to forest management, environment protection and landscape conservation. Maintaining the natural resource base and managing forests in a sustainable manner will require teaching programme combining policy and law, business economics and management, and forest resource and environmental economics components. Болонський процес призводить лісове господарство і лісову освіту в контекст розвитку глобальної економіки, а також всесвітньої турботи про захист середовища та зміни клімату. Це стимулює інтеграцію лісового господарства у мережу невиснажливого землекористування і поєднання досвіду лісового господарства та нових наукових знань і методології досліджень. лісовим професіоналам потрібні всебічні загальноосвітні знання, якщо вони мають утриматися на тлі швидко мінливих соціальних, економічних і політичних проблем. У той же час їм потрібно зрозуміти локальні й культурні аспекти лісового господарства, що розвивається. Це потребує об'єднаного підходу до управління лісами, захисту довкілля і збереження ландшафтів. Для підтримки основи природних ресурсів і лісів, в яких ведеться господарство, у невиснажливій формі необхідна викладацька програма, що об’єднує політику, закон, ділову економіку і управління, складові лісових ресурсів і екологічної економіки. Болонский процесс приводит лесное хозяйство и лесное образование в контекст развития глобальной экономики, а также всемирной заботы о защите окружающей среды и изменениях климата. Это стимулирует интеграцию лесного хозяйства в систему неистощимого землепользования и сочетание опыта лесного хозяйства, новых научных знаний и методологии исследований. Лесным профессионалам нужны всесторонние общеобразовательные знания, если они должны удержаться на фоне быстро меняющихся социальных, экономических и политических проблем. В то же время им нужно понять локальные и культурные аспекты развивающегося лесного хозяйства. Это требует объединенного подхода к управлению лесами, защите окружающей среды и сохранению ландшафтов. Для поддержания основы природных ресурсов и лесов, в которых ведется хозяйство, в неистощимой форме требуется программа преподавания, которая объединяет политику, закон, деловую экономику и управление, составные части лесных ресурсов и экологической экономики.